Kinetics of green solid-liquid extraction of andrographolide from Andrographis paniculata: effects of particle size and solid-liquid ratio - Abubakar, Umar Isah (Walter de Gruyter GmbH, 2015)
In this work, the influences of particle size and solid-liquid ratio on the kinetics of green solid-liquid extraction of andrographolide from Andrographis paniculata (AP) were investigated. Kinetic experiments were performed in a pressurized liquid extractor under isothermal conditions at 80°C by varying the average particle size and solid-liquid ratio at various times. The identification and quantification of andrographolide concentration in the water extracts were carried out using high-performance liquid chromatography (HPLC). Kinetic data were fitted into first-order and second-order kinetics models with good correlation coefficients and coefficients of determination. However, the second-order rate law shows a better agreement with the experimental data. It was found that the observed specific extraction rate constants, kobs, increased to nearly twofold from 6.53×10-4 l mg-1 min-1 to 1.28×10-3 l mg-1 min-1 for solid-liquid ratio of 1:10 g ml-1 when particle size was decreased from 1.200 mm to 0.175 mm. In addition, kobs increased over fivefold, 3.44×10-3 l mg-1 min-1 and almost fourfold, 4.96×10-3 l mg-1 min-1, for particle sizes of 1.200 mm and 0.175 mm with an overall rise of more than sevenfold when the solid-liquid ratio was increased to 1:50 g ml-1, respectively. Therefore, kobs significantly increases with a decrease in particle size and an increase in solid-liquid ratio